Sistem Informasi Manajemen Ternak Sapi Perah di AKA Milk Jakarta - Muhammad Heryan Chaniago; Faizatul Amalia; Agus Wahyu Widodo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
AKA Milk is a public dairy cattle company that handling from the process of production to selling the cow's milk to customers. In order to maintain the quality of milk production, the cattle care and handling have been done routinely. However, in practice of the cattle care and handling, it has never been well-documented. Therefore, it's difficult to track the handling record or the current condition of the dairy cattle. In addition to cattle care, matters relating to milk selling are also not well-documented. While, a fact stated by Purwatiningsih and Kia (2018) that the identification and recording of dairy cattle can help farmers in managing the farm and ease the process of managing cattle raising. To overcome the above problems, a management information system of dairy cattle was built using the SDLC Prototyping method. At the stage of analysis and design, a model that can facilitate communication between developers and stakeholder is built in order to find the best solution in a form of a web-based information system. Models used for analysis and design stage includes use cases, use case scenarios, sequence diagrams, class diagrams, and entity relationship diagrams. The implementation will be carried out after stakeholders approve the design by creating a system using codeigniter framework. After the implementation phase done, the system will be tested using white box testing with cyclomatic complexity method and basis path testing. Black box testing will be used to continue the test using decision table method and compatibility testing using the single factor coverage method. The test results close to 100% valid indicates that the system can work optimally in supporting farm activities of AKA Milk which includes dairy cattle data management, care and milking activities, milk selling activities to financial management.